Influence of social determinant on values formation in healthcare (The Journal of Psychology and Sociology, 2021)
The high level of economic and demographic development of the country does not guarantee the equality of its citizens with regard to health. Differentiation at the health level is not only related to ge- netic, behavioral or infrastructural factors; despite their importance, it also reflects the socio-economic differentiation of society. Thus, a social determinant of health appears – an idea of the living conditions of people from birth to old age.The World Health Organization defines health not only as the absence of disease and physical defects, but also as a state of complete physical, mental and social well-being. However, this definition does not allow us to single out a set of objective indicators by which it is possible to observe and assess health. Currently, there is no single comparative scale that determines the level of health, the develop- ment of which requires high-quality interdisciplinary research.The purpose of the article is to study the concept of the socio-economic determinant of population health and the definition of the classification. Using the examples of modern foreign studies linking spe- cific indicators of health or life expectancy with a number of social determinants, the nature of the influ- ence of socio-economic factors on the health of the population is revealed. Due to the lack of knowledge of the concept of the socio-economic factor of population health in Kazakhstan, this article is of interest to the Kazakhstan audience due to a broad review of theoretical and empirical works on this topic.Key words: social policy, the relationship between health and the socio-economic situation, in- equality in the health sector.